PET Imaging of Recurrent Medullary Thyroid Cancer - Simon, G. H.; Nitzsche, E. U.; Laubenberger, J. J.; Einert, Almut; Moser, E. (Nuklearmedizin - NuclearMedicine, 1996)
Medullary carcinoma of the thyroid gland is a rare tumor. Its prognosis is mainly linked to surgery, because there is no valid alternative therapy to improve patients outcome. In this report, we discuss the recurrence of such a tumor in a 64-year-old female, focusing on magnetic resonance imaging and positron emission tomography evaluation of this tumor.Das medulläre Schilddrüsenkarzinom ist ein seltener Tumor. Seine Prognose wird maßgeblich durch die frühzeitige operative Entfernung des Tumorgewebes bestimmt, weil alternative Therapieformen zur Verbesserung der Prognose nicht zur Verfügung stehen. Im vorliegenden Fallbericht werden am Beispiel einer 64jährigen Patientin die Möglichkeiten der Kernspintomographie und der Positronen-Emissions-Tomographie in der Diagnostik des Rezidivs diskutiert.
Keywords: Medullary thyroid carcinoma; recurrence; PET